1995
DOI: 10.1021/j100022a008
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Structure and Vibrational Spectra of Dimethoxydisulfane, (CH3O)2S2

Abstract: The gas-phase structure of dimethoxydisulfane (CHgCfhSa was determined by electron diffraction. The molecule is chainlike and of symmetry C\. Selected experimental geometrical parameters are d{SS) 196.0(3) pm, c?(SO) 165.3(3) pm, d(CO) 143.2(3) pm, a(OSS) 108.2(3)°, a(COS) 114.5(4)°, r(SS) 91(4)°, r(SO) ± 7(3)°. Abinitio MO calculations at the HF/6-311G** level resulted in three conformational isomers originating from rotation about the two SO bond axes. The most stable conformer among these is in keeping wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…The S–S bond length of ClSSCl is about 0.06 Å longer than that of FSSF whereas the valence angle α­(S–S–Cl) is comparable to the valence angle α­(S–S–F). These geometric parameters of ClSSCl are close to those of CH 3 OSSOCH 3 determined by electron diffraction …”
Section: Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The S–S bond length of ClSSCl is about 0.06 Å longer than that of FSSF whereas the valence angle α­(S–S–Cl) is comparable to the valence angle α­(S–S–F). These geometric parameters of ClSSCl are close to those of CH 3 OSSOCH 3 determined by electron diffraction …”
Section: Results and Discussionsupporting
confidence: 71%
“…These geometric parameters of ClSSCl are close to those of CH 3 OSSOCH 3 determined by electron diffraction. 8 ■ CONCLUSIONS Rotational spectra of diethyl disulfide were measured and assigned by pulsed-jet FTMW spectroscopy. Two conformers were detected in the supersonic expansion.…”
Section: As Shown Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This model (sometimes referred to as negative hyperconjugation) 10,11a,b parallels the one proposed to account for the barrier of the S−N, N−C(O)X, and P−N rotation processes. Such an approach also explains the observation that in dialkoxy disulfides (ROSSOR) the S−S bond length is shorter , and the S−S rotational barrier higher , than in dialkyl disulfides (RSSR). Therefore, the more electronegative a substituent X in a XSSX derivative, the lower the energy of the X−S antibonding σ* orbital is expected to be, ,11b, thus making the π-type bond stronger, due to the more efficient n,σ* overlapping.…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, it has been found that chalcogen–chalcogen interactions play a crucial role in the structure and reactivity of a great variety of chalcogen‐containing compounds 1,2. The chalcogen–chalcogen bonds in bivalent compounds (REE′R′, E, E′ = O, S, Se) are known to prefer gauche conformations, which is usually attributed to lone‐pair interactions 3. These interactions favor a dihedral angle of about 90°, and steric interactions between the substituents (R, R′) tend to increase this angle.…”
Section: Introductionmentioning
confidence: 99%